The importance of reminders and patient preferences to improve inhaler technique in older adults with COPD - Barnestein-Fonseca, P.; Cotta-Luque, VM.; Aguiar-Leiva, VP.; Leiva-Fernández, J.; Martos-Crespo, Francisco; Leiva-Fernández, F. (Frontiers in Pharmacology, 2023)
Objectives: Medication non-adherence in patients with chronic obstructive pulmonary disease (COPD) is common. The aim is to evaluate the efficacy of two interventions to improve the inhalation technique (IT) in patients with COPD. Also determine optimal IT reminder time and to test the role of preferences in the intervention selection. Method: Consecutive sampling of 726 COPD patients from TECEPOC-study (patients’ preference trial/comprehensive cohort design) and TIEPOC-study (randomised controlled trial) were assigned into either intervention-A (written information in a leaflet with instructions about correct IT), intervention B (intervention A + individual training by instructors) or control group. TECEPOC: strong preferences (PPS group) with two arms (intervention A -IAP- and intervention B -IBP-). Randomisation (RCT group) with three arms (control -CG-, intervention A -IAR- and intervention B -IBR-), so in the end this study had 5 arms. TIEPOC: Randomisation (RCT group) with three arms (control -CG-, intervention A -IAR- and intervention B -IBR-). Four visits were performed (baseline, 3, 6 and 12 months). Intention to treat principle. Results: 660 patients (90.9%) did not perform a correct IT at baseline 89.75% with Handihaler, 86,95% with Turbuhaler, 84,75% with Accuhaler and 87,35% with pMDI. A decrease in the slope of the curve (correct IT) was detected at 3 months follow-up. TECEPOC Study: RCT-cohorts: differences IBR versus CG (p<0.0001), NNT=3.22 (IC95%, 2.27-5.52), differences IBR versus IAR (p<0.0001) with a NNT = 3.57 (CI95%, 2.41-6.8), no differences IAR versus CG. PPS-cohorts: differences IBP versus IAP (p<0.0001), NNT=3.33 (IC95%, 2.32-5.55). TIEPOC Study: differences IBR versus CG (p<0.0001), NNT=1.74 (IC95%, 1.47-2.17), difference IBR versus IAR (p<0.0001), NNT=3.33 (CI 95%, 2.43-5.55), no difference IAR versus CG. Preferences improved 6.7% in the correct IT without statistical significance. Conclusion: Individual training significantly improves IT. Reminders every 3 months are recommended. Preferences do not influence the intervention effectiveness